+0  
 
0
108
1
avatar

Let q(x) = 5 -x^2. I have to evaluate and simplify the following:

 

(a) q(r)

 

(b) q(r) - 5

 

(c) q(r) q(5)

 

I got the following:

 

(a) \({\sqrt{5}}\)

 

(b) -(r)^2

 

(c) 5, -5

 

Is this right?

 Jul 9, 2020
 #1
avatar+21958 
+1

If  q(x)  =  5 - x2 

 

then:  q(r)  =  5 - r2            (substitue 'r' for 'x')

 

q(r) - 5  =  (5 - r2) - 5  =  -r2 

 

q(r) - q(5)  =  (5 - x2) - (5 - 52)  =   (5 - x2) - (5 - 25​)  =  (5 - x2) - (-20​) =  5 - x2 + 20  =  25 - x2  

 Jul 9, 2020

14 Online Users